1989
DOI: 10.3109/03005368909076506
|View full text |Cite
|
Sign up to set email alerts
|

The IHR-McCormick Automated Toy Discrimination test—description and initial evaluation

Abstract: McCormick's Toy Discrimination test allows a skilled audiologist to obtain word discrimination thresholds in quiet from children with mental ages of 2 years and above. A semi-automatic version of the test has been developed and evaluated by testing the hearing of 46 children and five adults. The equipment for the new version of the test both produces the stimuli and scores the responses, thereby reducing the burden on the tester. It is reliable and allows greater sensitivity than the manual test as well as sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…This was obtained from a sample of 703 children; again, this represents one of the largest normative studies published to date. Previous work on eight normally hearing adults by Ousey et al (1989) revealed a mean WRT of 18.6 dB (A). This suggests that the WRT of 5-year old children will improve by a further 5 dB as they reach adulthood.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This was obtained from a sample of 703 children; again, this represents one of the largest normative studies published to date. Previous work on eight normally hearing adults by Ousey et al (1989) revealed a mean WRT of 18.6 dB (A). This suggests that the WRT of 5-year old children will improve by a further 5 dB as they reach adulthood.…”
Section: Discussionmentioning
confidence: 90%
“…The study used an automated version of the McCormick toy discrimination test known as the Institute of Hearing Research (IHR)-McCormick automated toy discrimination test (ATT) ( Ousey et al, 1989 ; Palmer et al, 1991 ; Summerfield et al, 1994 ). The ATT measures the minimum sound level at which a child can identify words presented in quiet in the sound field.…”
Section: Methodsmentioning
confidence: 99%
“…Aided sound field threshold measurements were undertaken when using warble tone stimuli with the ESPrit 22 worn on optimum sensitivity setting for 0.5 to 4 kHz using the Institute of Hearing Research (IHR)/McCormick Automated Toy Discrimination Test warble tone facility (10). The warble generator provides sound field warble tones at 7 frequencies from 0.25 to 5 kHz at levels from 0 to 78 dB(A) in steps down to 1 dB.…”
Section: Protocolmentioning
confidence: 99%
“…As such, picture-identi cation tests have mostly been used (e.g. In England, an automated toy-identi cation speech test has been developed (Ousey et al, 1989) and a Dutch version is available (Crul et al, 1994). When the child recognizes the presented word, he or she has to point to the appropriate picture.…”
Section: Auditory Developmentmentioning
confidence: 99%